2019
DOI: 10.1007/s42399-019-00098-x
|View full text |Cite
|
Sign up to set email alerts
|

The Body Weight, Blood Pressure, and Biochemical Parameters of the Patients After Obesity Surgery

Abstract: The objective of this study is to observe whether the patients' loss weight is long term after bariatric surgery, as well as evaluating the blood pressure and certain chemical parameters. This retrospective study was carried out based on the files of 70 patients, who underwent laparoscopic sleeve gastrectomy (LSG) operation between January 2013 and December 2017. Paired sample t test and Wilcoxon tests were used for comparison of patients' weight, blood pressure, and other parameters related to obesity within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…and dyslipidemia (mean 71% improvement) 15 . In a study with 70 patients followed up after bariatric surgery, Kocaöz et al found that the patients developed a significant decrease in systolic BP, diastolic BP, FBG, HbA1c, fasting insulin, HOMA-IR, total-C, LDL-C and triglyceride levels, while a significant increase in HDL-C levels 16 . In a study by Son et al, 40 patients undergoing sleeve gastrectomy were divided into 3 groups (the group with HT, the group with type 2 DM and the group without a chronic disease), and revealed a significant decrease in systolic BP, diastolic BP, FBG, HbA1c, total-C, LDL-C and triglyceride levels, while a significant increase in HDL-C levels were detected in the postoperative controls of the patients 17 .…”
Section: Discussionmentioning
confidence: 99%
“…and dyslipidemia (mean 71% improvement) 15 . In a study with 70 patients followed up after bariatric surgery, Kocaöz et al found that the patients developed a significant decrease in systolic BP, diastolic BP, FBG, HbA1c, fasting insulin, HOMA-IR, total-C, LDL-C and triglyceride levels, while a significant increase in HDL-C levels 16 . In a study by Son et al, 40 patients undergoing sleeve gastrectomy were divided into 3 groups (the group with HT, the group with type 2 DM and the group without a chronic disease), and revealed a significant decrease in systolic BP, diastolic BP, FBG, HbA1c, total-C, LDL-C and triglyceride levels, while a significant increase in HDL-C levels were detected in the postoperative controls of the patients 17 .…”
Section: Discussionmentioning
confidence: 99%